Genetic diversity in sunflower (Helianthus annuus L.): GENETIC DIVERSITY IN SUNFLOWER - M MALLIK; N MANIVANNAN; R CHANDIRAKALA (Journal of Oilseeds Research, 2016)
A study was conducted to determine the diversity among sunflower genotypes using D2 analysis during kharif, 2014. Study of per se performance of genotype, ARM 243B showed superiority for head diameter, 100-seed weight, seed yield per plant, oil yield per plant and with moderate resistance to Alternaria leaf spot disease. This was followed by COSF 2B, COSF 7B, CSFI 5019, CSFI 5040, CSFI 5083, CSFI 5213, CSFI 5336 and TNHSF 239-68-1-1-1. These genotypes showed high oil yield per plant and few component traits with moderate resistance to Alternaria leaf spot disease. These genotypes can be used for increasing oil yield by hybridization for development of hybrids. Parental divergence study showed that 115 genotypes were grouped into nine clusters. Considering the cluster mean and divergence values, clusters VII and VIII were more diverse followed by clusters II and VIII, I and VIII, III and VIII, V and VIII and VI and VIII suggesting that hybridization between divergent groups may lead to more variability for the characters concerned. Among the diverse clusters, genotypes CSFI 13024 and TNHSF 239-68-1-1-1 of cluster VII and CSFI 13022, CSFI 13023, CSFI 13069 and CSFI 13071 of cluster VIII may be crossed to obtain wider variation in segregating population.